The analysis of working medium flow through flow cavity elements of pneumatic-hydraulic systems - A. S. Pugachuk; O. A. Vorozheeva; A. V. Chernyshev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the issues of modeling the flow of working medium in the working cavity of ball valves with various types of designs of locking elements: with turned and stamped ball. Special attention is paid to obtaining the characteristics of hydraulic resistance depending on the angle of rotation of the regulating element. Mathematical modeling of the gas flow process in the considered types of ball valves is carried out, pressures and velocities in the working cavity of ball valves are determined. The analysis of the obtained data made it possible to estimate the error of the computational method based on a comparison with the published experimental data. Recommendations on the use of ball valves with turned and extruded ball are given